Faktor-Faktor yang Mempengaruhi Penggunaan Aplikasi E-Wallet Dana Di Kota Samarinda - Rezki Aguswidya Utami; Irwansyah Irwansyah (JURNAL BISNIS DAN PEMBANGUNAN, 2022)
ABSTRACT This study develops the Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2) model. UTAUT 2 consists of the variables of performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, price value, habit, behavioral intention, and use behavior. This study aims to examine the effect of the factors in the UTAUT 2 model on user behavior in using the DANA e-wallet application.This study uses a quantitative approach with an explanatory type. A sample of 90 users of the DANA application in Samarinda City was selected by accidental sampling. The causality test uses partial least squares.The results showed that performance expectancy and price value have positive and significant effects on behavioral intention; habit and behavioral intention have positive and significant effects on use behavior; effort expectancy and facilitating conditions have negative and insignificant effects on use behavior; social influence has negative yet significant effect on behavioral intention; and hedonic motivation has positive but not significant effect on behavioral intention. Keywords: UTAUT 2, Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Conditions, Hedonic Motivation, Price Value, Habit, Behavioral Intention, Use Behavior